Resistance screening and in silico characterization of cloned novel RGA from multi-race resistant lentil germplasm against Fusarium wilt (Fusarium oxysporum f. sp. lentis) - Nishmitha, K.; Singh, Rakesh; Dubey, Sunil C.; Akthar, Jameel; Tripathi, Kuldeep; Kamil, Deeba (Frontiers in Plant Science, 2023)
Fusarium wilt caused by Fusarium oxysporum f. sp. lentis (Fol) is the most devastating disease of lentil present worldwide. Identification of multi-race fusarium wilt resistance genes and their incorporation into existing cultivars will help to reduce yield losses. In the present study, 100 lentil germplasms belonging to seven lentil species were screened against seven prevalent races of Fol, and accessions IC201561 (Lens culinaris subsp. culinaris), EC714243 (L. c. subsp. odemensis), and EC718238 (L. nigricans) were identified as resistant. The typical R gene codes for the nucleotide-binding site and leucine-rich repeats (NBS-LRR) at the C terminal are linked to either the Toll/interleukin 1-like receptor (TIR) or coiled coil (CC) at the N terminal. In the present study, degenerate primers, designed from the NBS region amplifying the P-loop to the GLPLA motif, isolated forty-five resistance gene analogues (RGAs) from identified resistant accessions. The sequence alignment identified both classes of RGAs, TIR and non-TIR, based on the presence of aspartate (D) and tryptophan (W) at the end of the kinase motif, respectively. The phylogenetic analysis grouped the RGAs into six classes, from LRGA1 to LRGA6, which determined the diversity of the RGAs present in the host. Grouping of the RGAs identified from Lens nigricans, LnRGA 2, 9, 13 with I2 revealed the structural similarity with the fusarium resistance gene. The similarity index ranged from 27.85% to 86.98% among the RGAs and from 26.83% to 49.41% among the known R genes, I2, Gpa2, M, and L6. The active binding sites present along the conserved motifs grouped the RGAs into 13 groups. ADP/ATP, being the potential ligand, determines the ATP binding and ATP hydrolysis activity of the RGAs. The isolated RGAs can be used to develop markers linked to the functional R gene. Furthermore, expression analysis and full-length gene isolation pave the path to identifying the molecular mechanism involved in resistance.